PENERAPAN PEMBELAJARAN KONTEKSTUAL BERBASIS OUTING CLASS UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD INPRES 117 BULUDOANG KECAMATAN BANGKALA BARAT KABUPATEN JENEPONTO - juslaini JUSLAINI; Nurhaedah Nurhaedah; Erma suryani sahabuddin (Universitas Negeri Makassar, 2023)
This research is a classroom action research that aims to find out the application of contextual learning based on Outing Class to improve student learning outcomes in natural science subjects for class V SD Inpres 117 Buludoang, West Bangkala District, Jeneponto Regency. The approach used is a qualitative approach consisting of 2 cycle, where each activity cycle includes planning, implementation, observation, and reflection activities. The focus of this research is the application of contextual learning based on Outing Class to improve student learning outcomes in natural science subjects for class V SD Inpres 117 Buludoang, West Bangkala District, Jeneponto Regency. The research subjects were teachers and fifth grade students in the even semester of the 2021/2022 school year, totaling 21 people. Data collection uses the format of observation, tests, and documentation. The data analysis used is qualitative. The results showed that there was an increase in learning in the application of contextual learning based on outing class both on teacher and student activities and student learning outcomes. The conclusion of this study is that teacher teaching activities and student learning activities have increased. Student learning outcomes in the first cycle are in the poor category, while in the second cycle student learning outcomes have increased in the good category of the percentage of completeness of student learning outcomes and the application of contextual learning media based on outing class in science learning can improve the learning outcomes of fifth grade students.